Inhibitory activities of platelet-rich and platelet-poor plasma on the growth- of pathogenic bacteria - Omid Maghsoudi; Reza Ranjbar; Seyyed Hesamoddin Mirjalili; Mahdi Fasihi Ramandi (Iranian Society of Pathology, 2017)
Background:The utility and efficacy of novel materials in tissue regeneration and antimicrobial therapy are contingent upon the employment of either blood derivatives rich in platelets or platelet-poor-plasma (PPP). This effect is largely mediated by the increased or decreased concentration of platelets in the plasma. The current study aimed to analyze and evaluate the impact of platelet-rich (PRP) or PPP on inhibiting the growth of human pathogenic bacteria and compare their effects with those of chloramphenicol and penicillin. Methods: In the current comparative study, PRP-1 was generated using 1-step blood centrifugation method; whereas, for PRP-2 and PPP the 2-step centrifugation protocol was used. The antimicrobial activity of PRP-1, 2, and PPP were tested on Staphylococcus aureus, Escherichia coli, Klebsiella pneumonia, Pseudomonas aeruginosa, Streptococcus agalactiae, Staphylococcus epidermidis, Shigella sp. and Serratia sp.Well diffusion and serial micro-dilution methods were used for this purpose. Chloramphenicol and penicillin susceptibility were tested using the disk diffusion method. Results: While whole blood (WB) and PPP had no discernible impact on the growth parameters of any of the bacteria tested in the current study,PRP-1 reduced the growth rate of a few selected strains. In addition, while PRP-2 clearly inhibited the growth of Shigella sp., E. coli, S. aureus, S. agalactiae, and S. epidermidis, it had no impact on the growth of K. pneumoniae, P. aeruginosa,andSerratia sp Conclusion: It can be claimed that there is a strong correlation between the concentration of platelets and the antibacterial activity of PRP.